Regulation of Metabolism by an Ensemble of Different Ion Channel Types: Excitation-Secretion Coupling Mechanisms of Adipokinetic Hormone Producing Cells in Drosophila - Perry, Rebecca J.; Saunders, Cecil J.; Nelson, Jonathan M.; Rizzo, Michael J.; Braco, Jason T.; Johnson, Erik C. (Frontiers in Physiology, 2020)
Adipokinetic Hormone (AKH) is the primary insect hormone that mobilizes stored energy and is functional equivalent to mammalian glucagon. While most studies have focused on exploring the functional roles of AKH, relatively little is known about how AKH secretion is regulated. We assessed the AKH transcriptome and mined the data set for specific insight into the identities of different ion channels expressed in this cell lineage. We found reliable expression of multiple ion channel genes with multiple members for each ionic species. Specifically, we found significant signals for 39 of the either known or suspected ion channel genes within the Drosophila genome. We next performed a targeted RNAi screen aimed to identify the functional contribution of these different ion channels that may participate in excitation-secretion coupling in AKH neuroendocrine cells. We assessed starvation survival, because changes in AKH signaling have previously been shown to impact starvation sensitivity. Genetic knockdown of three genes (Ca-Beta, Sur, and sei), in AKH expressing cells caused highly significant changes (P < .001) in both male and female lifespan, and knockdown of six other genes (Shaw, cac, Ih, NaCP60E, stj, and TASK6) caused significant changes (P < 0.05) in only female lifespan. Specifically, the genetic knockdown of Ca-Beta and Sur led to increases in starvation lifespan, whereas the knockdown of sei decreased starvation survivorship. Focusing on these three strongest candidates from the behavioral screen, we assessed other AKH-dependent phenotypes. The AKH hormone is required for starvation-induced hyperactivity, and we found that these three ion channel gene knockdowns changed activity profiles and further suggest a modulatory role of these channels in AKH release. We eliminated the possibility that these genetic elements caused AKH cell lethality, and using independent methods, we verified expression of these genes in AKH cells. Collectively, these results suggest a model of AKH-cell excitability and establish an experimental framework for evaluating intrinsic mechanisms of AKH release.